2022
DOI: 10.3748/wjg.v28.i36.5265
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 receptor as the regulator of T-cell function in intestinal barrier disruption

Abstract: The intestinal mucosa is a highly compartmentalized structure that forms a direct barrier between the host intestine and the environment, and its dysfunction could result in a serious disease. As T cells, which are important components of the mucosal immune system, interact with gut microbiota and maintain intestinal homeostasis, they may be involved in the process of intestinal barrier dysfunction. P2X7 receptor (P2X7R), a member of the P2X receptors family, mediates the effects of extracellular adenosine tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 178 publications
0
6
0
Order By: Relevance
“…P2X7R shedding has been implicated in chronic in ammation and neurodegenerative diseases(Jiang et al, 2022;Savio et al, 2018;Wang et al, 2017). Earlier in the in vitro study, we found enhanced P2X7R shedding after EtOH exposure[18].…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…P2X7R shedding has been implicated in chronic in ammation and neurodegenerative diseases(Jiang et al, 2022;Savio et al, 2018;Wang et al, 2017). Earlier in the in vitro study, we found enhanced P2X7R shedding after EtOH exposure[18].…”
mentioning
confidence: 54%
“…In chronic in ammation and neurodegenerative diseases, enhanced P2X7R shedding has been observed [71][72][73]. Additionally, in vitro dendritic cell P2X7R stimulation with ATP can trigger shedding of microvesicles carrying the P2X7R itself, suggesting a regulatory role of P2X7R signaling in its own shedding process [74].…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal barrier can be divided into four layers: the microbiological barrier, the mucosal barrier, the cellular barrier, and the immunological barrier ( Figure 3 ) [ 10 ]. The microbiological barrier is located in the outermost position of the mucus layer and is formed by the presence of microorganisms and their metabolites.…”
Section: Protective Effects Of Hcas On the Intestinal Barriermentioning
confidence: 99%
“…The intestinal barrier acts as a semipermeable membrane that allows the passage of nutrients while preventing the entry of pathogens and harmful substances. Dysfunction of the intestinal barrier can lead to increased intestinal permeability and contribute to the development of serious diseases [ 10 ]. In this regard, the metabolism of phenolic compounds in the gut has been shown to optimize intestinal barrier function, which is beneficial for preventing and treating enteropathy and systemic disorders associated with barrier disruption, such as chronic metabolic diseases, liver diseases, and encephalopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer has become a major threat to human lives. It has been estimated that worldwide there are ≈14.1 million new cases of cancer and that nearly 8.2 million people die from cancer each year, [ 1 ] In hospitals, surgical removal of tumors is one of the most frequently used and also highly effective methods for treating cancers, particularly solid tumors, [ 2 ] However, the postoperative recovery is still far from satisfactory for many cancer patients, [ 3 ] which is very often accompanied by a much‐lowered quality of life caused by tissue dysfunction or disability after the removal of tumor together with surrounding healthy tissue and/or high risk of cancer recurrence due to incomplete elimination of cancer cells. [ 4,5 ] Conventionally, postoperative radiotherapy and/or chemotherapy are provided to patients to reduce the risk of cancer recurrence, [ 6,7 ] while their inevitable side effects can impair wound healing and the repair/regeneration of tissue at the resection site.…”
Section: Introductionmentioning
confidence: 99%